Evaluation the potential of recombinant anti-CD3 nanobody on immunomodulatory function. (February 2020) - Moradi-Kalbolandi, Shima; Sharifi-K, Azadeh; Darvishi, Behrad; Majidzadeh-A, Keivan; jalili, Neda; Sadeghi, Solmaz; Mosayebzadeh, Marjan; Sanati, Hassan; Salehi, Malihe; Farahmand, Leila
Highlights: An anti-CD3 nanobody was constructed and successfully expressed. The purified anti-CD3 nanobody recognize native CD3 expressed on the cells. The purified anti-CD3 nanobody could effectively suppress tumor growth in tumor bearing balb/c mice. Our anti-CD3 nanobody could be a promising candidate for targeting and activating CTLs to induce anti-tumor responses. Abstract: T cells are the most predominant effector cells in immune-mediated elimination of cancer and circumventing tumor progression. Among various approaches, T cells activation by specific antibodies independently of their TCR specificity, is considered as an effective approach to circumvent tumor progression. The most common surface marker for all T cells which is crucial for T cell activation is regarded as CD3. Therefore, the goal of our study was to evaluate the preclinical efficacy of recombinant anti-CD3 nanobody. To this end, anti-CD3 sequence, was PCR amplified, following cloning and expression in E.coli and purification, the purified nanobody with a molecular weight of ∼17 kDa was confirmed by western blot. Furthermore, flow cytometry analysis demonstrated that purified nanobody could bind to CD3 on Jurkat cell line. Subsequently, results from inoculation of 3 μg/g of nanobody to tumor bearing balb/c mice indicate inhibition of tumor growth. Furthermore, circulating levels of tumoricidal cytokines such as IL-2 and IFNγ were raised whereas tolerogenic cytokines such as IL-4, 6 and 10 were decreased at the end of the treatment. Moreover, IHC analysis confirmed the presence and also the percentage of TILs in tumor sites in response to anti-CD3 therapy. Hence, our results suggest that the purified anti-CD3 nanobody may become a promising candidate for targeting and activating CTLs to induce anti-tumor responses and may provide groundwork for future studies involving other kind of cancers.